1994
DOI: 10.1080/00039896.1994.9940377
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Contamination and Assessment of Exposure to Antineoplastic Agents by Determination of Cyclophosphamide in Urine of Exposed Pharmacy Technicians: Is Skin Absorption an Important Exposure Route?

Abstract: In the Netherlands, special guidelines and safety precautions were introduced about 10 y ago for preparation and administration of antineoplastic agents. However, little is known about the effectiveness of these measures. In this study, occupational exposure to antineoplastic agents of nine pharmacy technicians who were involved in drug preparation was investigated. Cyclophosphamide, 5-fluorouracil, and methotrexate accounted for 95% of the antineoplastic agents prepared; therefore, the presence of these compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
110
3
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(120 citation statements)
references
References 6 publications
5
110
3
2
Order By: Relevance
“…Recent studies showed also that antineoplastic levels in air samples were not significantly detected, suggesting that inhalation might have a lower impact when assessing exposure (Mason et al 2005;Connor et al 2010;Huang et al 2012). Therefore, contact with contaminated workplace surfaces without gloves seems to play an important role in the dermal exposure to antineoplastic drugs (Hirst et al 1984;Sessink et al 1994;Kromhout et al 2000;Fransman et al 2005;Schierl et al 2009). In this context, most of the recently published studies give particular attention to the assessment of surfaces contamination and report a generalized contamination, even in hospitals with the best equipment and strict safety procedures (Turci et al 2003;Hedmer et al 2005;Mason et al 2005;Brouwers et al 2007;Hon et al 2011Hon et al , 2013Kopp et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed also that antineoplastic levels in air samples were not significantly detected, suggesting that inhalation might have a lower impact when assessing exposure (Mason et al 2005;Connor et al 2010;Huang et al 2012). Therefore, contact with contaminated workplace surfaces without gloves seems to play an important role in the dermal exposure to antineoplastic drugs (Hirst et al 1984;Sessink et al 1994;Kromhout et al 2000;Fransman et al 2005;Schierl et al 2009). In this context, most of the recently published studies give particular attention to the assessment of surfaces contamination and report a generalized contamination, even in hospitals with the best equipment and strict safety procedures (Turci et al 2003;Hedmer et al 2005;Mason et al 2005;Brouwers et al 2007;Hon et al 2011Hon et al , 2013Kopp et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This problem is notable because, although there are other routes of exposure, studies have indicated that dermal absorption is the main route of occupational exposure to antineoplastic drugs. [9][10][11][12] To the authors' knowledge, few studies have examined dermal contamination among hospital workers. In a study performed in the Netherlands, Fransman and others 13 found contamination on the hands of pharmacy technicians involved with drug preparation.…”
Section: Introductionmentioning
confidence: 99%
“…In a number of studies we have demonstrated that workers involved in the production, preparation and administration of antineoplastic agents are exposed to these drugs [5,[22][23][24][25][26][27][28][29]. The uptake was assessed by the determination of the parent drug or metabolite in the urine of the workers.…”
Section: Introductionmentioning
confidence: 99%
“…The uptake was assessed by the determination of the parent drug or metabolite in the urine of the workers. Large differences were found in urinary excretion of cyclophosphamide (CP) between several groups, suggesting variable exposure levels [5,23,24,26,28]. The question is whether these expo sure levels will cause nephrotoxic effects in the workers.…”
Section: Introductionmentioning
confidence: 99%